IMPROVING STUDENTS’ UNDERSTANDING OF ENGLISH PROVERBS THROUGH KAHOOT APPLICATION - Ami Pradana; Joko Prayudha.S; Tri Yuni Hestuti (Language and Education Journal, 2024)
One of the topics that students must learn in English literature class is English proverbs. Proverb is one of the old works of literature that students must master especially in English literature classrooms, as an elective subject in high school. This study aims to find out the improvement of students’ understanding of English proverbs by using the Kahoot application. The present research used Classroom Action Research (CAR) to help students improve their understanding of English proverb materials. The sample in this research is 36 students who have taken English literature at the school. Data was obtained through observation and tests about the implementation of English proverbs. This research uses the Arikunto stage. Each cycle consists of four stages, (1) the action planning stage, (2) the action implementation stage, (3) the observation and inner achievement stage, and (4) the analysis and reflection stage. Research instruments use student learning outcomes. Data analysis uses the percentage technique. The result explained that students’ understanding of English proverbs increased, namely, from cycle I of class X MIPA F, 23 students got a score of 77, with the KKM standard score of 75. In cycle II, 34 students got scores greater than 80, and the others got scores less than 80. Based on the actions taken, it can be concluded that the use of Kahoot applications can improve students’ understanding of English proverbs.